Living Qur’an sebagai Solusi Penguatan Pendidikan Akhlak terhadap Siswa: Perspektif Teori Thomas Lickona (Studi Kasus MTs Pesantren El-Madani Rawalo) - Winasih, Tia Mugi; Munfarida, Elya (Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2024)
Abstract Currently, the Living Qur'an is dominated by the scope of social research, namely the scope of the community in wider society. Formal education, especially in secondary schools, still rarely incorporates and preserves the Al-Qur'an in it, whether it is for the development of children's character, moral and spiritual values. In fact, the